UM ESTUDO SOBRE AS CONCEPÇÕES E PRÁTICAS DE PROFESSORES DA EDUCAÇÃO BÁSICA SOBRE O ENSINO ADAPTADO - Cleucimar Aparecida Pereira Prudente (2025)
This qualitative narrative research was linked to the Education, Childhood, and Diversities research line of the Postgraduate Program in Education at the Federal University of Mato Grosso do Sul, Três Lagoas campus (MS). Its objective was to understand the conceptions and practices of Basic Education teachers regarding the adaptation of teaching for students who are the target audience of Special Education. The study involved two regular classroom teachers who teach Portuguese Language and Mathematics and have students with special education needs in their classes. As a data production instrument, conversation circles were held in the school setting, by appointment with the participating teachers. The discussions were based on three predefined thematic axes that covered the central elements of the proposed investigation: teachers' conceptions of school inclusion; teaching practices; and teachers' initial, continuing, and other training on school inclusion. The interpretation of the data produced was based on the researcher's narrative production, drawing from the theoretical frameworks used in the study. As a result, it was possible to conclude that the conceptions and practices of Basic Education teachers regarding the adaptation of teaching for students who are the target audience of Special Education are based on training focused on the Medical Model of disability interpretation, which significantly and directly influences their pedagogical practices. The concept of inclusion held by the teachers was actually geared towards integration, as they idealize a student model and propose adapting teaching for those who do not fit the idealized profile, which cannot be considered an inclusive practice. Due to a lack of knowledge, they do not challenge the mistaken guidance they receive with suggestions for adapting activities for students with special education needs. They believe that a specialist advisor in Special Education would be sufficient to deal with the challenges encountered in the classroom, as they feel they lack clarity on the best way to include everyone. It is therefore possible to conclude that the conceptions and practices of the investigated network are often contradictory and not always aligned with inclusion. The research also revealed that teachers are aware of how flawed the initial, continuing, and other training they receive from the State Secretary of Education is regarding school inclusion, and as a result, the school scenario does not change.